1999
DOI: 10.1046/j.1365-2486.1999.00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Biotic, abiotic and performance aspects of the Nevada Desert Free‐Air CO2 Enrichment (FACE) Facility

Abstract: Summary Arid and semiarid climates comprise roughly 40% of the earth’s terrestrial surface. Deserts are predicted to be extremely responsive to global change because they are stressful environments where small absolute changes in water availability or use represent large proportional changes. Water and carbon dioxide fluxes are inherently coupled in plant growth.  No documented global change has been more substantial or more rapid than the increase in atmospheric CO2. Free Air CO2 Enrichment (FACE) technology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
147
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 105 publications
(154 citation statements)
references
References 20 publications
7
147
0
Order By: Relevance
“…On 22-23 June and 8-9 September 1999, measurements were conducted at the Nevada Desert Free Atmospheric carbon dioxide (CO 2 ) Exchange Facility (NDFF) near Mercury, NV in the Mojave Desert (361E49 0 N, 1151E55 0 W, 965-970 m ASL). The shrub community was characterized as a Larrea-Ambrosia-Lycium species complex (Jordan et al, 1999). Annual precipitation is $8 cm, and occurs mostly as rainfall during the winter months.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On 22-23 June and 8-9 September 1999, measurements were conducted at the Nevada Desert Free Atmospheric carbon dioxide (CO 2 ) Exchange Facility (NDFF) near Mercury, NV in the Mojave Desert (361E49 0 N, 1151E55 0 W, 965-970 m ASL). The shrub community was characterized as a Larrea-Ambrosia-Lycium species complex (Jordan et al, 1999). Annual precipitation is $8 cm, and occurs mostly as rainfall during the winter months.…”
Section: Methodsmentioning
confidence: 99%
“…Arid and semi-arid ecosystems (those receiving o30 cm of precipitation yr À1 ), on the other hand, have received very little study. Although foliar biomass density of arid ecosystems is low compared to forest systems (Box, 1981), they occupy $40% of the Earth's terrestrial surface area (Jordan et al, 1999) and typically receive abundant sunshine and warm temperatures throughout much of the year. Here, we present BVOC emission measurements from the most abundant plant species near Tucson, AZ and Mercury, NV, USA.…”
Section: Introductionmentioning
confidence: 99%
“…Precipitation during the study is shown in Fig. 1 sparse with < 20% of surface area covered by shrubs and perennial plants (Jordan et al, 1999). The NDFF data used in this study consists of six plots, each a ring of 23 m diameter.…”
Section: Field Datamentioning
confidence: 99%
“…It is also one of only two operational FACE experiments in a natural, unmanaged ecosystem (Nowak et al 2004). The experiment is composed of three 25-m diameter plots maintained at a CO 2 set point of 550 ppm, three plots with the FACE apparatus but maintained at ambient CO 2 (blower controls), and three plots without the FACE apparatus (non-blower controls) (Jordan et al 1999). The vegetation of the NDFF is characteristic of the Mojave Desert and is dominated by the xerophytic shrubs Ambrosia dumosa (bur-sage) and Larrea tridentata (creosote bush).…”
Section: The Nevada Desert Face Facilitymentioning
confidence: 99%